The USA-Africa command and USA foreign policy on Africa - Fixter, Charlene (My University, 2016)
The establishment of AFRICOM was met with a wave of criticism from African leaders as well as from members within the American government. Despite the seemingly lofty declarations by the USA about the purpose of AFRICOM, the enthusiasm was not shared by all African leaders. This study explored the reasons for the establishment of the USA-Africa Command, AFRICOM. In doing so, it also examined the reaction of African leaders after the announcement of the establishment of AFRICOM. The study further looked at the reasons behind the lack of appreciation by African leaders for a unilateral decision by the USA to establish a military Command on the African continent. This study further investigated whether the USA military footprint in Africa increased since the establishment of AFRICOM as well as the security implications for Africa since AFRICOM’s establishment. Thus the study confirmed an earlier assertion that AFRICOM needs to stabilise the African continent for USA’s economic onslaught. The initial fears of USA’s interference and dominance on the continent is thus far unfounded, as unified African opposition to AFRICOM forced the USA to change track regarding some of its plans regarding AFRICOM. An initial charge that AFRICOM is another form of colonisation of Africa by the USA cannot be borne out by this research. The study showed that significant developments took place in Africa in the last decade, changing it from a “hopeless” continent to a continent “rising”. This has focused the world’s attention, such as superpowers like USA and China, and emerging giants like Russia, Brazil and India, on Africa. This led to a dramatic shift in USA foreign policy towards Africa, giving rise to the birth of AFRICOM in 2007.
Research report submitted to the University of the Witwatersrand School of Governance, Johannesburg, in partial fulfilment for the Masters of Management (Public and Development Management). Masters of Management in Security March 2015